2023
DOI: 10.1021/acs.jpcc.3c05164
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Evolution Reaction Performance of Nickel (Hydr)Oxide in Alkaline Media: Iron and Nickel Impurities

Mahya Salmanion,
Mohammad Mahdi Najafpour

Abstract: This study explores the mysteries of the oxygen-evolution reaction (OER) in the presence of Ni(Fe) (hydr)oxides and examines the effects of Ni and Fe impurities on the reaction. The current methods for removing Fe impurities could complicate the study of OER. A crucial aspect of this study is the reinvestigation of Ni (hydr)oxides in a Ni/Fe-free electrolyte during the OER. It is widely recognized that a Ni (hydr)oxide phase, possessing an active phase for the OER, forms on the surface of Ni foil in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Pure Ni (hydr)oxide lacks substantial activity, indicating it requires Fe to achieve high catalytic levels. 7 Fe species tend to leach out from the Ni environment over time, 9 leading to a decline in catalytic activity as the synergistic effects diminish. Over time, Fe species may also agglomerate, reducing surface area and reactivity, and leading to decreased catalytic efficiency.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Pure Ni (hydr)oxide lacks substantial activity, indicating it requires Fe to achieve high catalytic levels. 7 Fe species tend to leach out from the Ni environment over time, 9 leading to a decline in catalytic activity as the synergistic effects diminish. Over time, Fe species may also agglomerate, reducing surface area and reactivity, and leading to decreased catalytic efficiency.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Despite numerous studies on the fundamental, structural, and electronic bulk properties of LaNi x Fe 1– x O 3 , information on the origin of the activity, the nature of the active species, and the role of the A site is still elusive and unclear. Although there is much evidence for the influence of the electrolyte impurities on the active Ni sites, the dependence of the soluble Ni species in the electrolyte on the active Fe sites is challenging and still under discussion. Ye et al have reported the effect of Ni and Fe on Ni­(OH) 2 /NiOOH films. They found out that the presence of Ni impurities hindered the electrocatalytic performance .…”
Section: Introductionmentioning
confidence: 99%
“…While water splitting is a promising strategy for hydrogen production, the oxygen-evolution reaction (OER) facilitated by the water-oxidation reaction remains a bottleneck. Similar to Ni/Fe, Cu/Fe-based compounds, Cu/Fe (hydr)oxides, have shown potential as effective catalysts for OER. Interestingly, some Cu complexes break down into Cu (hydr)oxide under OER conditions, which then acts as the true catalyst. The influence of Fe in the OER processes of metal oxides has also gained interest. The effect of Fe in the OER involving Ni oxide has been thoroughly investigated. , However, research on Fe’s impact on Cu (hydr)oxide OER is limited. , Indeed, the addition of a small amount of Fe ions to Cu (hydr)oxide showed high OER activity at alkaline conditions. , However, Cu (hydr)oxide tends to dissolve, complicating observations of Fe’s role. Boettcher’s research team observed that the OER performance of Fe oxide varies across different substrates, ranking from highest to lowest as Au > Pd ≈ Cu ≈ Pt > Cat at pH 14 (with pH 13 for Cu) . They attributed these differences to the variable adhesion strengths of Fe hydroxide across these substrates, suggesting that both adsorption strength and charge transport at the Fe oxide/substrate interfaces are influenced by these variations .…”
Section: Introductionmentioning
confidence: 99%